2005
DOI: 10.1002/jms.908
|View full text |Cite
|
Sign up to set email alerts
|

A high‐pressure mass spectrometric and density functional theory investigation of the thermochemical properties and structure of protonated dimers and trimers of glycine

Abstract: A new modification of pulsed-ionization high-pressure mass spectrometry (PHPMS) has been used to perform equilibrium thermochemical studies for relatively nonvolatile biomolecules such as amino acids. Binding enthalpy and entropy changes have been measured for proton-bound clusters of glycine, which are in good agreement with both theoretical (DFT) results of this work and a previous blackbody infrared dissociation experiment. Experimental data indicate that a number of conformers of the proton-bound dimer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 27 publications
5
30
0
Order By: Relevance
“…Recently, the proton-bound dimers of the simplest aliphatic amino acids were reported in the 700-2000 cm À1 region as well as the glycine proton-bound dimer in the O-H/N-H stretching region (Atkins et al, 2008). These spectroscopic studies confirmed previous thermochemical and computational studies (Raspopov & McMahon, 2005) which proposed that the structures of these species are ion-dipole complexes between a N-protonated amino acid and the carboxyl end of the other amino acid rather than proton-bound dimers bound by the amino groups of both amino acids. The spectrum of the proton-bound glycine dimer in the high-energy region also showed evidence for very strong intramolecular hydrogen bonding in the form of broad bands extending down to 2800 cm À1 as well as an absorption assigned to the shared proton stretching vibration.…”
Section: Infrared Spectroscopy Of Biologically Significant Ionssupporting
confidence: 82%
“…Recently, the proton-bound dimers of the simplest aliphatic amino acids were reported in the 700-2000 cm À1 region as well as the glycine proton-bound dimer in the O-H/N-H stretching region (Atkins et al, 2008). These spectroscopic studies confirmed previous thermochemical and computational studies (Raspopov & McMahon, 2005) which proposed that the structures of these species are ion-dipole complexes between a N-protonated amino acid and the carboxyl end of the other amino acid rather than proton-bound dimers bound by the amino groups of both amino acids. The spectrum of the proton-bound glycine dimer in the high-energy region also showed evidence for very strong intramolecular hydrogen bonding in the form of broad bands extending down to 2800 cm À1 as well as an absorption assigned to the shared proton stretching vibration.…”
Section: Infrared Spectroscopy Of Biologically Significant Ionssupporting
confidence: 82%
“…By contrast, in aqueous solution, the reverse stability order is observed and the question of as to whether a comparable situation exists inside protonated clusters may be asked. Indeed several recent studies show that the two forms, covalent and zwitterionic, may intervene in clusters (Julian, Hodyss, & Beauchamp, 2001; Raspopov & McMahon, 2005; Wu & McMahon, 2005). The thermochemistry of gas‐phase interaction between protonated glycine and ammonia has been studied both experimentally by high‐pressure mass spectrometry and theoretically (Wu & McMahon, 2005).…”
Section: Structural and Energetic Aspects Of The Protonationmentioning
confidence: 99%
“…For instance, a high-pressure mass spectrometric and density functional theory investigation of the thermochemical properties and structure of protonated dimers and trimers of glycine was reported by Raspopov and McMahon. [38] Atkins et al [39] carried out a IR multiple photon dissociation spectra study on proton-and sodium-ion-bound glycine dimers.…”
mentioning
confidence: 99%